Evaluation of the Potential Impact of Wildfires on Buried Natural Gas Pipelines - Dylan Bernard; Clement Chanut; Vincent Blanchetiere; Frederic Heymes (Chemical Engineering Transactions)
This study assesses the potential impact of wildfires on buried natural gas pipelines, a key concern as wildfires become more frequent and intense, particularly in regions where gas infrastructure intersects with wildfire-prone areas. The aim is to evaluate the thermal effects of the incident heat flux from wildfires on the soil above pipelines and the soil temperature distribution. A simplified approach is used for rapid analysis based on hypotheses about flame front geometry and soil thermal properties. A parametric study shows that even under worst-case conditions (high incident heat flux and prolonged fire exposure), soil temperatures at the depth of the pipeline remain below critical thresholds. As a result, the current burial depth standards of 0.8 m provide significant protection against hypothetical severe thermal damage from wildfires, reinforcing their continued effectiveness in safeguarding buried gas facilities in wildland fire-prone areas. This conclusion appears to be theoretically validated in scenarios where the maintenance strip is properly maintained. Further studies will be conducted to examine the opposite situation, i.e., where no cleared maintenance strip is present.